Clinical presentation and outcomes of diabetic ketoacidosis in pediatric and adolescent patients at a tertiary hospital in Jordan - Al Thiabat, Hanan; Elbanna, Sara; Quadier, Mohammad; Dayyeh, Mohmmad; Abunnadi, Bashar; Obeidat, Hadeel; Abu Shakhdam, Ala'a; Elfarraj, Hala; Almomani, Miral A.; Abu-Ekteish, Faisal (Frontiers in Pediatrics, 2025)
IntroductionDiabetic ketoacidosis (DKA) remains a serious and potentially life-threatening complication of diabetes in children and adolescents, particularly in resource-limited settings, with overall mortality of 3.4%–13.4% in developing countries. Understanding the clinical presentation, treatment outcomes, and complication rates is essential to improving care and reducing morbidity.MethodsA retrospective analysis was conducted on pediatric patients aged 2–16 years admitted with DKA to King Abdulla University Hospital (KAUH) between 2017 and 2023. Data were collected on age, diagnosis status, DKA severity, and clinical outcomes.ResultsDKA was most common between 6 and 12 years old (67.8%) with mean age of 9 (IQR = 5). More than two thirds of children were newly diagnosed upon admission (72.4%) while the remainder were known cases of T1DM, 41.1% of patients had severe DKA while 35.7% had moderate DKA. No mortality was reported during the study period.ConclusionDKA remains a frequent presentation among newly diagnosed pediatric diabetes cases in this setting, with a high proportion of moderate to severe presentations. Despite the severity, no deaths were reported, highlighting the effectiveness of management protocols at KAUH. Continued efforts are needed to improve early diagnosis and reduce complication rates.